2016
DOI: 10.3855/jidc.6118
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics and pathogens attributable to hand, foot, and mouth disease in Shanghai, 2008–2013

Abstract: Introduction: Hand, foot, and mouth disease (HFMD) is a common childhood illness caused by enteroviruses. A passive surveillance system has been implemented in Shanghai Pudong since 2008 and etiology surveillance since 2009.We characterized the epidemiology and the etiology of HFMD in Pudong from 2008-2013. Methodology: Health care providers were required to report any clinically diagnosed HFMD to Pudong District Center for Disease Control and Prevention. For all severe cases and randomly selected mild HFMD ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
3
4
0
Order By: Relevance
“…Statistical analysis of the age and gender distribution in the present study showed that children under age five were the most susceptible to HFMD, which is consistent with previous reports 19 , 28 , 43 , 44 . Male predominance of HFMD was observed both in severe and mild cases in our study, possibly because of higher activity and poorer hygiene 45 , 46 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Statistical analysis of the age and gender distribution in the present study showed that children under age five were the most susceptible to HFMD, which is consistent with previous reports 19 , 28 , 43 , 44 . Male predominance of HFMD was observed both in severe and mild cases in our study, possibly because of higher activity and poorer hygiene 45 , 46 .…”
Section: Discussionsupporting
confidence: 93%
“…Since the latter half of 2012, however, the positive rates of non-EV71 and non-CV-A16 EV-associated HFMD have grown rapidly, and these viruses became major factors in the Shanghai HFMD epidemic. Similar trends were also reported in Shanghai 28 30 and other cities in China 12 18 , 31 , 32 . Recently, CV-A6 displaced EV71 and CV-A16 to become the predominant enteroviral serotype in Shanghai.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Although immunogenicity in the maternal serum has been examined in some reports, the pattern of immune responses against HFMD has not been well examined. In this study, we observed that the expression of IgM was high over 0 ‐96 hours followed by a gradual decline, whereas the expression of IgG was the opposite, with a gradual increase over time.…”
Section: Discussionmentioning
confidence: 99%
“…Neutralization titers were determined as the highest serum dilution that could prevent the appearance of a CPE in 50% of the cell cultures (performed in quadruplicate). The lowest dilution at which a CPE was observed in >50% of wells was considered the antibody titer of the serum sample, and a titer ≥1:8 was considered the cutoff for a positive antibody response …”
Section: Methodsmentioning
confidence: 99%